2020
DOI: 10.3390/s20051401
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Development of Tunable Graphene Nanoantennas for Terahertz Optoelectronic and Plasmonic Applications

Abstract: Exceptional advancement has been made in the development of graphene optical nanoantennas. They are incorporated with optoelectronic devices for plasmonics application and have been an active research area across the globe. The interest in graphene plasmonic devices is driven by the different applications they have empowered, such as ultrafast nanodevices, photodetection, energy harvesting, biosensing, biomedical imaging and high-speed terahertz communications. In this article, the aim is to provide a detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 331 publications
(404 reference statements)
0
61
0
Order By: Relevance
“…The realization of ultrafast plasmons-based optical signal source at the nanoscale is considered as a longstanding goal, the potential of the graphene-based emitter to revolutionize optoelectronics, thus allowing ultrafast optical signal processing for communication [ 49 ]. When the electron beam is exposed to the optically excited surface plasmons of graphene, the unidirectional, chromatic, and tunable emission from IR to X-ray was realized from the graphene [ 50 , 51 , 52 ]. The theoretical investigation and experimental demonstration of this mechanism predict the existence of plasmons at VIS and IR wavelengths [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The realization of ultrafast plasmons-based optical signal source at the nanoscale is considered as a longstanding goal, the potential of the graphene-based emitter to revolutionize optoelectronics, thus allowing ultrafast optical signal processing for communication [ 49 ]. When the electron beam is exposed to the optically excited surface plasmons of graphene, the unidirectional, chromatic, and tunable emission from IR to X-ray was realized from the graphene [ 50 , 51 , 52 ]. The theoretical investigation and experimental demonstration of this mechanism predict the existence of plasmons at VIS and IR wavelengths [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The photocarrier concentrations of the four models at 60 mW/mm 2 are listed in Table 2, which are calculated from Equation (1). The enhanced multireflection between the surface nanostructures and the specific surface area enables strong light absorption.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Terahertz (THz) radiation (0.1~10 THz) triggers a great number of intriguing and complex physical, biological, and chemical phenomena. It consequently possesses wide practical application prospects in communications, spectroscopy, and imaging [1][2][3][4][5][6][7]. For THz imaging purposes, a THz spatial light modulator (SLM) is involved, which requires the THz modulator to be fast and efficient.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion relation of the graphene presented by Equation (29) can be reduced to the ordinary TL model dispersion relation as, βp = √ LC, when the resistance R = 0 is considered in Equation (29). Applying the Fabry-Perot type resonator condition on graphene hexagon having an effective length, Equation 29becomes…”
Section: Resonant Frequency Calculation Of Graphene Hexagone Based Onmentioning
confidence: 99%
“…The absorption efficiency that was attained at the infrared region is tuned from 3% to 30% with tightly packed graphene nanodisks. Furthermore, various studies are reported by utilizing different graphene nanostructures to enhance the absorption along with enhancement of electric field [23,25,29]. Gric et al [30], use the approach of photo-conductive antennas that is based on the optimized plasmonic nanostructure to numerically study the absorption enhancement in nanocylinders, where the absorption amplituide and resonant wavelength can be affected by the thickness and separation of nano cylinders.…”
Section: Introductionmentioning
confidence: 99%